Implementasi Internet of Things pada Alat Pemberi Pakan Ternak Ikan Otomatis di Peternakan Lele UD. Nasrullah - Rizaldy Khair; Iswandi Idris; Mirwan Aziz Ritonga (Mahesa Research Institute, 2022)
Manufacture of an IoT-based automatic animal feeder at the UD catfish farm. Nasrullah is to make it easier for catfish farmers in providing animal feed, this tool will provide feed according to a predetermined time so as to reduce the mistakes of farmers who sometimes forget to provide animal feed, besides that this tool also uses an IoT basis so that farmers can change the feed schedule and provide feed manually by pressing the button on the smartphone. This automatic fish feeder was made using NodeMCU as a controller, RTC Module as a timer, Servo as the opening and closing of the feed container, and Android Studio IDE to create software that controls the tool, and Arduino IDE to enter commands to the controller.